IMPLEMENTASI 4 C DALAM PENDIDIKAN PANCASILA BERBASIS STEAM - Danang Prastyo; Trisa Kumalasari; Samsiah Samsiah; Siti Lebar (Universitas Islam Lamongan, 2021)
21st century skills called 4Cs, in Indonesian can be remembered by the abbreviation 4K, namely creativity, critical, communication, cooperation. This is in line with Bloom's theory that creativity is the highest ability in the aspect of cognitive development. Therefore, it is important to give creativity to Early Childhood Education. The research method uses descriptive quantitative. Grand design with pretest and post test with 25 children as respondents. The results showed that there was a significant difference to 4K in children before receiving treatment and after receiving the STEAM method application. This study aims to test the effectiveness of STEAM in increasing 4K for children in learning PANCASILA during the pandemic. STEAM in its application cannot be separated from loosepart which can increase children's creativity. High creativity benchmarks are characterized by increased thinking skills, flexible thinking skills, original thinking skills and detailed thinking skills. The application of the STEAM method in the implementation of learning can improve children's abilities marked by being able to solve problems and being able to make relationships with the surrounding environment, especially knowledge in PANCASILA.